(untitled) (R&D Journal, 2022)
This study investigates the potential gains in operating volume flow rate and static efficiency of an induced draught axial flow fan system. These gains are achieved through pressure recovery, i.e. the conversion of dynamic pressure at the fan exit into static pressure. Pressure recovery is achieved using downstream diffusers, stator blade rows, and combinations of these. Three different diffuser lengths are considered. Of the shortest diffusers, a conical diffuser increases the operating volume flow rate by 3.2 % and the fan static efficiency by 9.8 % (absolute). A longer conical diffuser increases it by 3.9 % and 11.9 %, respectively. Of the longest diffusers, an annular diffuser increases the flow rate by 5.5 % and the fan static efficiency by 16.8 %.